Routledge handbook of peacebuilding - Mac Ginty, Roger, 1970- (Routledge, 2013)
"This new Routledge Handbook offers a comprehensive, state-of-the-art overview of the meanings and uses of the term 'peacebuilding', and presents cutting-edge debates on the practices conducted in the name of peacebuilding. The term 'peacebuilding' has had remarkable staying power. Other terms, such as 'conflict resolution' have waned in popularity, while the acceptance and use of the term 'peacebuilding' has grown to the extent that it is the hegemonic and over-arching term for many forms of mediation, reconciliation and strategies to induce peace. Despite this, however, it is rarely defined and often used to mean different things to different audiences. Routledge Handbook of Peacebuilding aims to be a one-stop comprehensive resource on the literature and practices of contemporary peacebuilding. The book is organised into six key sections: - Section 1: Reading peacebuilding - Section 2: Approaches and cross-cutting themes - Section 3: Disciplinary approaches to peacebuilding - Section 4: Violence and security - Section 5: Everyday living and peacebuilding - Section 6: The infrastructure of peacebuilding This new Handbook will be essential reading for students of peacebuilding, mediation and post-conflict reconstruction, and of great interest to students of statebuilding, intervention, civil wars, conflict resolution, war and conflict studies and IR in general"--Resumé vydavatele